Exploring Assessment and Feedback: EFL E-Learning in Saboyá during Covid-19 (2023)
During the Covid-19 pandemic, teachers from a rural institution in Saboyá experienced a negative impact on their academic processes due to limited student access to the internet. The objective of this research was to identify and analyze the assessment strategies, mediated in e-learning, for English as a foreign language classes in a rural school. This investigation was based on a qualitative case study in which teachers from the institution voluntarily participated. The information was collected through questionnaires, artifacts, and field notes, and was analyzed through a triangulation process. The results revealed that the assessment strategy employed in this institution focused on the development of worksheets exchanged throughout WhatsApp. Consequently, the assessment had a primarily summative orientation. Furthermore, communication was limited to phone calls which resulted in a deficiency in the feedback process